HIV self-testing: South African young adults' recommendations for ease of use, test kit contents, accessibility, and supportive resources - Tiarney D. Ritchwood; Amanda Selin; Audrey Pettifor; Sheri A. Lippman; Hailey Gilmore; Linda Kimaru; Jennifer Hove; Ryan Wagner; Rhian Twine; Kathleen Kahn (BMC, 2019)
Abstract Background The uptake of HIV self-testing (HIVST) could address socio-structural barriers that prevent South African youth from utilizing the testing resources available in their communities. However, to facilitate this, we must tailor components of the HIVST kit and process to ensure that we reach and encourage youth to test. The purpose of this study to elucidate concerns and issues regarding HIVST rollout among South African youth. Methods This study was conducted in two phases: 1) focus group discussions with rural, South African youth aged 18-24 and 2) direct observations of participants completing with an oral HIVST kit and/or a blood based HIVST kit. In phase 2a participants were invited to try both an oral and blood-based HIVST kit. In phase 2b, participants selected the HIVST kit of their choice. Results We enrolled 35 unique participants in phase 1, 20 participants in phase 2a, and 40 participants in phase 2b. While the focus group discussions highlighted hypothetical HIVST use only, participants appreciated the privacy that the HIVST could afford them. However, they expressed concerns about whether HIVST could be trusted due to false positives and negatives, as well as whether a person would be able to emotionally handle the results if they tested alone. They suggested that the kits be used alongside someone who could provide support. In phases 2a and 2b, participants were overwhelmingly positive about both kits regarding ease of use and whether their results could be trusted. The participants, however, experienced more challenges with the blood-based versus oral test. When given the choice in phase 2b, most participants (80%) chose the oral HIVST over the blood-based HIVST. Conclusions During the focus group discussions, participants raised concerns about the validity of HIVST, lack of emotional support when testing alone, and the cost of HIVST kits, all of which could be addressed through current testing campaigns. Most of those who actually tested had positive experiences with HIVST and would recommend it to their friends. When offered a choice, most preferred the oral test. Trial registration NCT03162965, registered 19th May 2017.